STRATEGI PENURUNAN EMISI METANA PADA PADI SAWAH ORGANIK SEBAGAI UPAYA OPTIMALISASI PERTANIAN BERKELANJUTAN - Mumpuni, Restu Puji; Pratama, Agief Julio; Nurulhaq, Muhammad Iqbal; Dewi, Ratih Kemala; Wiraguna, Edi; Situmeang, Widya Hasian; Budiarto, Tri; Mardisiwi, Ririh Sekar (RISALAH KEBIJAKAN PERTANIAN DAN LINGKUNGAN Rumusan Kajian Strategis Bidang Pertanian dan Lingkungan, 2025)
The agricultural sector, especially rice fields, contributes to greenhouse gas emissions, especially methane gas. Methane gas is produced from the anaerobic decomposition of organic matter around rice plants’ roots, especially those continuously flooded. The addition of organic matter in organic rice is also a contributor to methane gas. Strategies to reduce methane emissions in organic rice cultivation need to be carried out, especially now that organic rice products have added economic value and better competitiveness, especially with increasing public awareness of healthy and environmentally friendly products. Some efforts to reduce methane emissions include intermittent irrigation of rice, selection of rice varieties that are more resistant to waterlogging and short-lived, the need to properly manage crop residues by composting them, and careful use of organic fertilizers that can help reduce methane emissions. Combining various cultivation strategies that reduce methane emission production can increase the sustainability of organic wetland rice systems and support climate-smart agriculture programs.